1985
DOI: 10.1111/j.1469-7610.1985.tb01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Iq, Scholastic Performance and Behaviour of Sibs Raised in Contrasting Environments

Abstract: Medium- and long-term effects of types of placement of the offspring of lower class families have been studied. The progeny of 28 mothers was reconstituted. The subjects were divided into three groups: 35 children abandoned and adopted early in privileged environments (A), 46 'biological mother-reared' children remaining in their disadvantaged social environments (B) and 21 children raised in institutions or foster homes (C). Analyses focused on IQ, scholastic performance and behaviour. Results show that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 18 publications
4
37
0
3
Order By: Relevance
“…The lower test-retest correlations for VTs than for children in the Scarr et al study may partly reflect the VTs' younger age at participation. The higher IQ scores and larger IQ gains obtained by biological children than by adoptive children are consistent with previous reports from this study, and with extant studies (see Cardon, 1994;Dumaret & Stewart, 1985). The VTs' parents generally held professional, technical or managerial positions or, if not employed outside the home, had earned higher educational degrees.…”
Section: Discussionsupporting
confidence: 91%
“…The lower test-retest correlations for VTs than for children in the Scarr et al study may partly reflect the VTs' younger age at participation. The higher IQ scores and larger IQ gains obtained by biological children than by adoptive children are consistent with previous reports from this study, and with extant studies (see Cardon, 1994;Dumaret & Stewart, 1985). The VTs' parents generally held professional, technical or managerial positions or, if not employed outside the home, had earned higher educational degrees.…”
Section: Discussionsupporting
confidence: 91%
“…French national adoption studies, using a sibling-proband design, found that infant adoption had a positive effect on children's cognitive development, and that this process was positively correlated with the socio-educational background of the adoptive family [26,27]. The results were also replicated in a study of late adoptions (4-6 years) of neglected or abused children [28].…”
Section: Discussionmentioning
confidence: 84%
“…But considering that other studies have reported on foster children's over time deteriorating school performances (eg. Dumaret, 1985), it seems likely that the Skolfam model did make a difference.…”
Section: Limitations/methodological Issuesmentioning
confidence: 99%